Europium incorporated in silica matrix obtained by sol-gel: luminescent materials - Nassar, Eduardo José; Ciuffi, Katia Jorge; Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP] (ABM, ABC, ABPol, 2003)
In this work we report some aspects of the chemistry involved in the preparation of modified silicon oxide by the sol-gel process. Europium III compounds were used as luminescent probe. An organic-inorganic hybrid was obtained by hydrolysis of tetraethylorthosilicate (TEOS) and 3-aminopropyltriethoxysilane (APTS). The Eu III compounds were added in different ways. In the first, silica was prepared in the presence of Eu III, and in the second, Eu III was added on the silica surface. These materials were studied by luminescence, infrared spectroscopy and termogravimetric analysis. The results obtained for the hybrid material show different behavior for Eu III emission, which could be excited by the antenna effect and the influence of the surrounding in the luminescence quenching. The thermogravimetric data present different mass loss in samples to range temperature 50 - 150 °C. Thermogravimetric and infrared spectra showed that inorganic polymers incorporated the organic part.
Keywords: sol-gel; luminescence; surface modified; silica